Strategy To Strengthen The Impact Of Indonesian Sustainable Palm Oil (ISPO) Implementation On Independent Smallholder Palm Oil Farmers - Bustomi, Muhamad Yazid; Pratama, Adnan Putra; Kamarati, Kiamah Fathirizki Agsa; Sardianti, Andi Lelanovita; Lisnawati, Andi; Abidin, Zainal; Syauqi, Anis (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Environmentally friendly and sustainable palm oil management is one way that can be done in the face of competition for palm oil products produced. The Indonesian sustainable palm oil (ISPO) certification is the standard used in Indonesia, which needs effort and support from various parties. The purpose of this study was to formulate a strategy to strengthen the impact of ISPO implementation on KUD Bumi Subur Kertabumi Village Kuaro District Paser Regency. The research was conducted in July 2024. Data collection methods through surveys, and interviews with the help of questionnaires. In addition, focus group discussions were also conducted with smallholders and experts to formulate alternative strategies. The data analysis method used is the analytic hierarchy process (AHP) method for weighing alternative strategies to strengthen the impact of ISPO implementation. The results showed that alternative strategies for strengthening socio-economic impacts were based on the criteria of human resource management, with the alternative of smallholders understanding the standards of ISPO implementation. At the same time, strengthening environmental impacts on waste management criteria, namely distinguishing hazardous waste (B3) as an alternative strategy. Each alternative in the criteria is mutually supportive and related, but smallholders can determine the things that are prioritized to be done.